Looking back : the Northern Territory in 1888 - Dixon, Val.; Historical Society of the Northern Territory (Casuarina, N.T. : Historical Society of the Northern Territory, 1988)
Chapter by Tony Austin annotated separately.
Available from The Manager, Historical Society of the Northern Territory, P.O. Box 40544, Casuarina, N.T. 0811.
Errata slip inserted.
Includes bibliographies.
Keywords: Northern Territory -- History -- 1824-1900.; Northern Territory (NT)